Seeking forgiveness: factor structure in samples from Latin America, Africa, Asia, and Southern Europe - Felix Neto (2013)
The study examined, using confirmatory factor analyses, the three-factor structure of the Disposition to Seek Forgiveness Questionnaire - inability in seeking forgiveness, sensitivity to circumstances before seeking forgiveness, and unconditional seeking of forgiveness - among samples from Latin America (Brazil), Africa (Angola and Mozambique), Asia (Indonesia), and Southern Europe (Portugal). It was found that this ternary structure has cross-cultural generality.